Technology Impact on I.T. Ethics Decisions in China - Siu, Donald Tsun-Kwan (My University, 2012)
Information and communications technology played a significant role in the recent economic growth of China, the second largest economy in the world. As a result, China faces many social and ethical challenges common to technology-advanced countries. Ethical reasoning and practices are often influenced by cultural expectations and regional norms. The purpose of this study was to investigate how IT knowledge, and IT experience may affect IT ethics decision making.
Color poster with text, graphs, photographs, and charts.
Keywords: Management information systems; Business ethics--China; Posters